2018
DOI: 10.3390/ijerph15081660
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Prediction of MTHFR Gene Polymorphism and Air Pollution on the Risks of Congenital Heart Defects Worldwide: A Transgenerational Analysis

Abstract: Congenital heart disease (CHD) is the leading cause of death in children, and is affected by genetic and environmental factors. To investigate the association of air pollution with methylene-tetrahydrofolate reductase (MTHFR) polymorphisms and the risk of CHD, we included 58 study groups of children and parents, with 12,347 cases and 18,106 controls worldwide. Both MTHFR C677T (rs 1801133) and A1298C (rs 1801131) gene polymorphisms were risks for CHD in children with transgenerational effects from their parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…In MTHFR , which encodes methylenetetrahydrofolate reductase, 2 polymorphisms, C677T and A1298C, have been investigated. Eleven meta-analyses have investigated the association of congenital diseases with C677T, 54 55 56 57 58 59 60 61 62 63 64 All meta-analyses analyzed the risk of CHD and only 1 study examined both congenital heart disease and orofacial cleft. Three studies showed no significant association between C677T and congenital heart disease, while 7 studies described a positive association with these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In MTHFR , which encodes methylenetetrahydrofolate reductase, 2 polymorphisms, C677T and A1298C, have been investigated. Eleven meta-analyses have investigated the association of congenital diseases with C677T, 54 55 56 57 58 59 60 61 62 63 64 All meta-analyses analyzed the risk of CHD and only 1 study examined both congenital heart disease and orofacial cleft. Three studies showed no significant association between C677T and congenital heart disease, while 7 studies described a positive association with these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, Chen et al 54 reported 2 negative ORs, for the recessive model and for the homozygote model, each based on 6 case-control studies. Yang et al 57 conducted a meta-analysis using 42 studies; both MTHFR C677T and A1298C polymorphisms were associated with the risk of CHD. 56 A TT model (pooled RR, 1.30; 95% CI, 1.14–1.48) and a TT+CT model (pooled RR, 1.09; 95% CI, 1.04–1.14) showed a significant positive relationship with congenital heart disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the association between the MTHFR C677T polymorphism and the risk of CHDs, but the results have been inconsistent (Hobbs et al, 2005; Zhu et al, 2006; Brandalize et al, 2009; Božović et al, 2011). Meta-analyses showed that maternal MTHFR C677T polymorphism may contribute to the risk of CHDs (Wang et al, 2013; Xuan et al, 2014; Yang et al, 2018). Research on the relationship between the maternal MTHFR genotype and the development of CHD in children with DS has also yielded conflicting results (Brandalize et al, 2009; Hobbs et al, 2010; Božović et al, 2011; Elsayed et al, 2014; Coppedè, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined gene-environment interactions to identify those who may be more susceptible to the effects of air pollution with respect to risk of birth defects. One recent study performed a meta-prediction analysis to compare countries with different proportions of methylene-tetrahydrofolate reductase (MTHFR) polymorphisms and air pollution exposure and risk of congenital heart defects (Yang, Yang, Yu, & Shiao, 2018). This study observed percentages of the TT and CT genotypes, relative to the CC genotype of the MTHFR gene, were increased in countries with higher levels of air pollution, with a trend of increased congenital heart defects risks with higher levels of air pollution.…”
Section: Introductionmentioning
confidence: 99%